PENDAMPINGA N BELAJAR ANAK DENGA N METODE AKSI (AKTIF, KREATIF, SANTAI, DA N INOVATIF) UNTUK MENINGKATKA N MINAT BELAJAR ANAK DI DESA MUARA GADING MAS - Septiana Fatika Setianingrum; Muhammmad Rifahdli Yusuf; Andrian Febriansyah; Dwi Yanti Wahyu Lestari; Tyas ariyati; Rahaf Maryam sugiarto; Silvi Arlita Saputri (Universitas Ichsan Sidenreng Rappang, 2024)
The aim of the Rumah Mengajar Program is to provide tutoring to childre n aged 6-12 years i n Muara Gading Mas Village to provide learning. The objects of this research are childre n i n Muara Gading Mas Village. The results of this research are learning guidance provided by IAI N Metro Period III KPM (Community Service Lecture) students using the AKSI method to increase children's interest i n participating i n learning. ACTIO N (active, creative, relaxed and innovative) is a strategy i n teaching that makes the atmosphere i n the teaching and learning process safe and comfortable so that the learning carried out by students is focused. The learning process carried out by teachers currently tends to be teacher-dominated activities. The Rumah Mengajar program uses the classroom actio n research method. The existence of a teaching program ca n help childre n i n the learning process, such as providing assistance and guidance i n the learning process which aims to increase students' enthusiasm and interest i n learning. Mentoring and guidance for childre n is focused o n students at Balai Tiyuh Muara Gading Mas, teaching childre n religio n at Musola Baitu n nur Dusu n 2 Muara Gading Mas Village, and providing study guidance at the KPM post which ca n increase the enthusiasm and togetherness of childre n and students.